OPTIMUM DISTANCE BETWEEN VORTEX GENERATORS USED IN MODERN THERMAL SYSTEMS - Akcayoglu, Azize; Ozgun, Cenap; Nazli, Celal; Yilmaz, Fuat; Pinarbasi, Ali (European Scientific Journal, ESJ, 2014)
Modern thermal systems in which hydrodynamics and thermal fields are strongly related to each other involve compactness and effective heating/cooling performance. Triangular ducts, having delta-wing type vortex generators (VGs) mounted on the ductâ€™s slant surfaces, are widely used in modern thermal systems including gas turbines and electronics cooling applications. Due to the existence of completely opposite results obtained in terms of performance of the two types of VG configurations â€“namely â€œflow upâ€ and â€œflow downâ€-, in the open literature, in the present study, both hydrodynamics and thermal fields together with the secondary flows induced by the VGs have been analysed extensively to understand which configuration has the better thermo-hydraulic performance. The results show that one configuration has a 19% higher thermo-hydraulic performance over 32 different VG configurations -containing â€œflow-upâ€ and â€œflow-downâ€- for hydraulic diameter based Reynolds number, Re=5000. The angle of inclination of each VG made with the flow direction is set to 30Â° and the inclined surfaceâ€™s wall temperatures are set to 80Â°C. Based on the current results, the optimum distance between successive VGs has been determined as 0.385 of the hydraulic diameter. The present CFD results have been validated against the PIV data